Learning Environment Design and Use (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Amid burgeoning international interest in the built environment of education, this SI examines the research, policy, and practice that lies behind the global trends in architecture and pedagogy. It contributes to the developing interdisciplinary understanding of the processes and products of school design at all stages, from ‘visioning’ and brief, through habitation and use, to post-occupancy evaluation. The intention is to build knowledge relating to successful design, educational affordances and outcomes, change management, and the alignment of physical resources with teaching and learning needs. The papers explore the multiprofessional landscape of educational spaces as they are planned, built, and used. Reflecting the diversity of the area, the SI features empirical work using a range of methodologies, transdisciplinary work and novel theoretical framings. It includes co-authored papers whose authorship bridges academic disciplines, research and practice, or research and policy. The over-arching aim was to capture the diversity of research related to learning environments.